2010
DOI: 10.1186/1472-6750-10-10
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput detection of mutations responsible for childhood hearing loss using resequencing microarrays

Abstract: BackgroundDespite current knowledge of mutations in 45 genes that can cause nonsyndromic sensorineural hearing loss (SNHL), no unified clinical test has been developed that can comprehensively detect mutations in multiple genes. We therefore designed Affymetrix resequencing microarrays capable of resequencing 13 genes mutated in SNHL (GJB2, GJB6, CDH23, KCNE1, KCNQ1, MYO7A, OTOF, PDS, MYO6, SLC26A5, TMIE, TMPRSS3, USH1C). We present results from hearing loss arrays developed in two different research facilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 34 publications
4
48
0
1
Order By: Relevance
“…However, the SureSelectIllumina method is superior in terms of scalability, cost, and increased sensitivity. Our results compare very favorably with recent reports of high-throughput diagnostic tests for NSHL that rely on primer extension arrays (26) or targeted resequencing arrays (27), which are appealing due to low cost but are limited in terms of capacity (not all NSHL genes can be screened simultaneously) and therefore sensitivity.…”
Section: Discussionsupporting
confidence: 76%
“…However, the SureSelectIllumina method is superior in terms of scalability, cost, and increased sensitivity. Our results compare very favorably with recent reports of high-throughput diagnostic tests for NSHL that rely on primer extension arrays (26) or targeted resequencing arrays (27), which are appealing due to low cost but are limited in terms of capacity (not all NSHL genes can be screened simultaneously) and therefore sensitivity.…”
Section: Discussionsupporting
confidence: 76%
“…For our ResAT data, the detection rate of nucleotide substitutions in the automated mode was higher, and that in the manual mode was slightly lower, compared with detection rates in previous studies (82.1 vs. 81%, respectively, in automated mode, and 97.4 vs. 100%, respectively, in manual mode) (Bruce et al 2010;Chiou et al 2011). Our ResAT analysis was unable to detect any small indel mutations; this is similar to other studies (Hartmann et al 2009;Kothiyal et al 2010). In the human gene mutation database (HGMD; http://www.hgmd.cf.ac.uk/ac/index.…”
Section: Discussionsupporting
confidence: 66%
“…This technology has been used for multiple-gene analysis in childhood hearing loss (Kothiyal et al 2010), breast-ovarian cancer syndrome (Schroeder et al 2010), dilated cardiomyopathy (Zimmerman et al 2010), X-linked intellectual disability (Jensen et al 2011), familial hypercholesterolemia (Chiou et al 2011), and hypertrophic cardiomyopathy (Fokstuen et al 2011). DiVerent research groups have shown ResAT to be a highly eYcient, relatively accurate, cost-eVective, and rapid method.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Laboratory for Molecular Medicine of Partners Healthcare Center for Personalized Genetic Medicine (PCPGM) offers physicians access to 33 genetic diagnostic and screening tests for hearing loss [46] or University of Iowa that have developed a software, AudioGene, to predict AD non-syndromic HL [47].…”
Section: Diagnostic Methods and Screeningmentioning
confidence: 99%